PENERAPAN MODEL PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PESERTA DIDIK - Empat Patonah (Jurnal Redox, 2019)
This research was conducted due to the lack of development of students 'science process skills in chemistry lessons, which was due to the Teacher Centered learning process which resulted in students' scientific process skills not developing properly. The Process Oriented Guided Inquiry Learning (POGIL) learning model is used as an alternative to problem solving which aims to determine whether or not there is an increase in students' science process skills through the application of the POGIL learning model. The research method used is a quasi-experimental method with a non-equivalent type of control group design. The sample was taken by purposive sampling and divided into two groups, namely the control class and the experimental class. Data collection techniques were obtained through test instruments and science process skills observation sheets. The data analysis technique used was the n-gain test, independent t-test and correlation. The results of the n-gain test were 0.78 with high criteria, for the independent t-test the sig value was obtained. (2-tailed) = 0.000 and the results of the correlation test obtained a correlation coefficient = 0.942 which is included in the very good category. These data results indicate that there is a high increase in students' science process skills with the application of the POGIL learning model, and the results of the independent t-test show that there is a significant difference in results between the experimental and control classes. As well as improving science process skills, it has a very good and meaningful relationship with the knowledge of students through the application of the POGIL learning model. Keywords: Process Oriented Guided Inquiry Learning (POGIL) learning model, Science Process Skills, Hydrocarbons